Cutaneous T-cell lymphoma of mycosis fungoides type with CD30 positive transformation and sweet like neutrophilic dermatosis. (October 2021) - André, Florine; Biogazi, Sofia; Leuenberger, Mathieu; Gaide, Olivier; De Leval, Laurence; Hohl, Daniel; Prins, Christa; Gillet, Michel; Guenova, Emmanuella
Abstract : Introduction: Cutaneous lymphomas are malignancies of T- or B-cell origin, with the majority of cases of approximately 75% being cutaneous T-cell lymphomas (CTCL). The main subtype of CTCL include the most frequent mycosis fungoides (MF), accounting for approximately 60% of CTCL. Mycosis fungoides is most often indolent but patients with advanced disease and especially transformed disease with large atypical, often CD30+ lymphocytes have a poor prognosis. The association of neutrophilic dermatosis (ND) with various hematologic disorders is well documented but uncommon with CTCL. Case report: An 80 years old woman was admitted for fulminant MF associated to Sweet-like ND not responding to systemic corticosteroids and methotrexate. Clinical symptoms (fever, painful skin nodules) and laboratory parameters (lymphocytosis and neutrophilia) were compatible with Sweet syndrome. Skin histology demonstrated dense, atypical lymphocytic infiltrate and numerous admixed lymphocytes. However, edema in the upper dermis, which is a histological hallmark of Sweet syndrome, was never present in the skin biopsies. After establishing diagnosis of transformed CD30+ MF with concomitant Sweet-like ND, treatment with Brentuximab was initiated and resulted in initial remission with reduction of mSWAT down to 30% from June 2020 to November 2020. However, after 6 cycles of Brentuximab, the MF progressed with new nodular ulcerated lesions, fierce itching and severe skin tenderness. Further, the disease was complicated by a superinfection and sepsis driven by methicillin resistant staphylococcus aureus, and later on pseudomonas aeruginosa. The MF related Sweet-like ND aggravated, paralleled by an overall decrease in the patient's condition. Chemotherapy was contraindicated in the context of infectious complications and deteriorated general condition. As a therapeutic alternative, we initiated a palliative radiotherapy, however, there was a fulminant disease progression and the patient deceased shortly after. Conclusion: The association of MF with ND is rare, underreported and seems to be related to poorer prognosis, resistance to treatment and impaired quality of life.